2014
DOI: 10.14231/ag-2014-023
|View full text |Cite
|
Sign up to set email alerts
|

Mukai's program for curves on a K3 surface

Abstract: Let C be a general element in the locus of curves in Mg lying on some K3 surface, where g is congruent to 3 mod 4 and greater than or equal to 15. Following Mukai's ideas, we show how to reconstruct the K3 surface as a Fourier-Mukai transform of a Brill-Noether locus of rank two vector bundles on C.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
64
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(65 citation statements)
references
References 12 publications
1
64
0
Order By: Relevance
“…We will therefore first develop some auxiliary results on E 2k+2,2 . Recall that by [7] these spaces are irreducible and that H ∼ kE 1…”
Section: A Technical Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We will therefore first develop some auxiliary results on E 2k+2,2 . Recall that by [7] these spaces are irreducible and that H ∼ kE 1…”
Section: A Technical Resultsmentioning
confidence: 99%
“…We find α = 0 as above. We have 2F 1 (20)). It follows that h i (2 F 1 +2 F 2 − H) = 0 for i = 0, 1 and h 0 (4 F 1 +4 F 2 − H) = 2, whence β = 2 by (14).…”
Section: Fiber Dimensions Of Moduli Mapsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using that X has Picard number 1 and B 2 is 20 or at least 24, Arbarello-Bruno-Sernesi and Feyzbakhsh showed that C lies on a unique K3 surface of Picard number 1 [2],…”
Section: Bott Vanishing For Ksurfaces Of Picard Numbermentioning
confidence: 99%
“…For the other compact examples, taking their dual fibrations seems to produce new examples of Lagrangian fibrations, making this a potentially fertile direction to explore. 2 The GL-Hitchin system…”
Section: Introductionmentioning
confidence: 99%